Diminishing social inequality between refugee children and their peers growing up in Denmark. Issue 7 (18th May 2020) - de Montgomery, Christopher J.; Petersen, Jørgen Holm; Jervelund, Signe Smith
ABSTRACT: Not being in employment, education or training (NEET) as a youth consistently predicts adverse educational, labour market and health outcomes. School-aged refugee children are known to be particularly vulnerable within each of these domains. Yet little is known about how these outcomes have evolved over time. This study explores trends in the risk of youth NEET status during the early twenties for refugees and their non-refugee peers in Denmark from 1995 to 2014 by utilising national registry data on demographics, income, education and diagnoses covering the full population. The analysis shows that the inequality in the probability of youth NEET status has diminished considerably from up to 20 percentage points among the oldest cohorts to less than 5 percentage points among the youngest. This development was robust to compositional differences, although much more so for girls than boys. For refugee girls, the change in the probability of youth NEET status coincided with changes in timing of family formation, but was not explained by it. In addition, the correlation between family formation and youth NEET status became considerably weaker over time. The findings suggest that some circumstances surrounding the incorporation of refugee school children into their new social contexts have improved.